Examining differences in exposure to digital marketing of unhealthy foods reported by Canadian children and adolescents in two policy environments - Laura Vergeer; Carolina Soto; Mariangela Bagnato; Elise Pauzé; Ashley Amson; Tim Ramsay; Dana Lee Olstad; Vivian Welch; Monique Potvin Kent (BMC Nutrition)
Abstract Background There has been relatively little research on youth’s exposure to food marketing on digital media, which is important as new digital platforms emerge and youth spend more time online. Evidence evaluating different policy approaches to restricting digital food marketing to children is also limited. This study examined differences in self-reported exposure to digital food marketing between children and adolescents in different policy environments: Ontario (where food marketing is self-regulated) and Quebec (where advertising is government regulated). Methods An observational cross-sectional online survey was conducted in April 2023 among children (aged 10–12 years) and adolescents (13–17 years) from Ontario and Quebec, recruited by Leger Marketing. Participants self-reported their frequency of exposure to food marketing via various digital platforms and marketing techniques. Logistic regression and proportional odds models examined differences in exposure by province and age group, adjusting for sociodemographic characteristics and digital device usage. Results The odds of reporting more frequent exposure to marketing of sugary drinks (OR: 0.48; 95% CI: 0.33, 0.69), sugary cereals (OR: 0.59; 95% CI: 0.41, 0.86), salty/savoury snacks (OR: 0.67; 95% CI: 0.47, 0.96), fast food (OR: 0.65; 95% CI: 0.45, 0.92), and desserts/sweet treats (OR: 0.54; 95% CI: 0.37, 0.78) were lower among Quebec children than Ontario children. Quebec children were less likely than Ontario children (OR: 0.56; 95% CI: 0.38, 0.84), but more likely than Quebec adolescents (OR: 1.58; 95% CI: 1.04, 2.42), to report exposure to unhealthy food marketing on one or more gaming/TV/music streaming platform/website(s). Compared with Ontario children, Quebec children were less likely to report exposure to marketing featuring characters or child/teenage actors (OR: 0.51; 95% CI: 0.34, 0.76), child-appealing subjects, themes and language (OR: 0.59; 95% CI: 0.40, 0.89), and visual design, audio and special effects (OR: 0.64; 95% CI: 0.41, 0.99), and to report exposure to a greater number of marketing techniques (OR: 0.60; 95% CI: 0.43, 0.84). Conclusions Exposure to unhealthy food marketing on digital media is high for youth from Ontario and Quebec, particularly for Ontario children. These findings reinforce the need for federal regulations to protect Canadian youth from unhealthy food marketing on digital media.